Proceso de atención de enfermería en gestante de 22 semanas con pieloninifritis. - Tomala Sanunga, Ckristhel Andrea (2021)
Pyelonephritis or high urinary tract infection is a kidney infection involving the renal parenchyma, renal pelvis, and renal calyxes. Normally, the microorganisms that produce it, ascend from the bladder to the parenchyma Pyelonephritis or high urinary tract infection is a kidney infection involving the renal parenchyma, renal pelvis, and renal calyxes. Normally, the microorganisms that produce it, ascend from the bladder to the parenchyma. However, it is important to know that urinary tract infections is one of the most frequent problems during pregnancy making this problem a more frequent reason for consultation in health centers especially for pregnant women, being the main cause those infections that are caused by large negative or great positive bacteria. (Portnov, Last revised: 16.04.2020). Among the clinical pictures presents pain when urinating, fever, chills, pain in the flank and lumbar area, nausea and vomiting. (Portnov, Last revised: 16.04.2020). Thus, this pathology is fundamentally female. The ratio of boys/girls is also higher in infants (1.51). In the rest of the ages the predominance is female, the pre-school age, 4.5% of girls and 0.5% of boys suffer from infection (ratio: 1/10). schoolchildren, the ratio of boys/girls is 1/30, adults, almost 50% of the population females suffer from at least one infection, 3-5% suffer from recurrent infections, compared to 0.1% of adult males (ratio: 1/50). Although in the elderly the disproportion decreases (110 in the group of 60-70 years), it is equal in hospitalized elderly patients. (BOVILLE). The nursing care process was developed in a 20-year-old female patient with a 22-week pregnancy plus pyeloneinphritis with the aim of contributing to improving the patient's health status through the development and execution of the nursing care plan. According to the needs of the patient.